2009
DOI: 10.1589/jpts.21.99
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Dual-Task on the Center of Pressure Trajectory of Healthy Young Adults during Obstacle Crossing

Abstract: Abstract.[Purpose] The purpose of this study was to examine the center of pressure (COP) trajectory and response time when young adults initiate gait and step over an obstacle while simultaneously performing a secondary Stroop task.[Subjects] Twenty healthy young adults (ten males and ten females) participated in the study.[Methods] The subjects first completed a Stroop task while standing (baseline) and then initiated gait and stepped over an obstacle at a self-paced speed with and without a secondary Stroop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The finding of increased COP displacement in the M-L direction and length of the COP path is similar to a previous report that the M-L displacement of COP and the length of the COP path were increased in subjects performing gait initiation or obstacle crossing with a concurrent secondary task 42) . In the current study, subjects appeared to have less postural control, which was manifest as an increase in the amplitude of the displacements of COP in the M-L and A-P directions when performing the stair descent with the concurrent secondary Stroop task.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding of increased COP displacement in the M-L direction and length of the COP path is similar to a previous report that the M-L displacement of COP and the length of the COP path were increased in subjects performing gait initiation or obstacle crossing with a concurrent secondary task 42) . In the current study, subjects appeared to have less postural control, which was manifest as an increase in the amplitude of the displacements of COP in the M-L and A-P directions when performing the stair descent with the concurrent secondary Stroop task.…”
Section: Discussionsupporting
confidence: 90%
“…Another study observed that older women had slower verbal reaction times than younger women and longer reaction times in a sitting position than in a standing position 41) . Kim 42) also demonstrated that the response time for obstacle crossing when a secondary Stroop task was provided was significantly longer than the response time in static standing only.…”
Section: Discussionmentioning
confidence: 97%
“…Significant correlations between kinetic events, time to stepping-limb TO, amplitude and duration of TA, and intended velocity of GI have been reported 5 ) . Similar patterns of modulation seem to occur when stepping to a new height 15 ) or over an obstacle 7 , 16 , 17 , 18 , 19 , 20 , 21 ) .…”
Section: Introductionmentioning
confidence: 67%